Preventive health programs for dairy cattle - Gerald L. Stokka; John F. Smith; James R. Dunham; Anne T. Van (Kansas Agricultural Experiment Station Research Reports, 1996)
Always consult your veterinarian when making vaccination decisions. The most common errors are failing to give booster immunizations and doing so at the incorrect time. Animal comfort is a greater determinant of production than vaccinations, and to receive the full benefits of nutrition, genetic, and management programs, cow comfort must be maximized. This does not lessen the need for balanced rations that allow the immune system to respond efficiently to vaccines. More is not necessarily better. The best vaccination program for a dairy includes vaccines for the most probable infectious pathogens possibly found in the herd. This combination is different for each production unit based on disease problems and management practices that can be identified by your herd practitioner.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Health; Vaccination